2010
DOI: 10.2136/sssaj2009.0126
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Coated Urea Maintains Potato Yields and Reduces Nitrous Oxide Emissions in a Minnesota Loamy Sand

Abstract: Irrigated potato (Solanum tuberosum L.) production requires large inputs of N, and therefore has high potential for N loss including emissions of N2O. Two strategies for reducing N loss include split applications of conventional fertilizers, and single applications of polymer‐coated urea (PCU), both of which aim to better match the timing of N availability with plant demand. The objective of this 3‐yr study was to compare N2O emissions and potato yields following a conventional split application (CSA) using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
77
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 26 publications
9
77
1
3
Order By: Relevance
“…Increasing the rate of N application, depending on soil C availability, may exponentially increase N 2 O emission (Kim et al, 2013). Thus, slow N release from CRFs or split application of N can reduce N 2 O emissions depending of environmental conditions and product properties (Akiyama et al, 2010;Burton et al, 2008;Halvorson et al, 2014;Hyatt et al, 2010;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the rate of N application, depending on soil C availability, may exponentially increase N 2 O emission (Kim et al, 2013). Thus, slow N release from CRFs or split application of N can reduce N 2 O emissions depending of environmental conditions and product properties (Akiyama et al, 2010;Burton et al, 2008;Halvorson et al, 2014;Hyatt et al, 2010;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Akiyama et al (2010) compiled data from 35 studies to evaluate CRF effects in N 2 O emissions and found an overall reduction of 35% compared with conventional and organic sources of N. The N release synchronized with plant demand can increase N use efficiency and thereby reduce N 2 O emissions (Hyatt et al, 2010;Yang et al, 2012). Controlledrelease fertilizers have small market participation because of high prices, but their importance has increased due to agronomic and environmental benefits (Chien et al, 2009).…”
mentioning
confidence: 99%
“…Jiménez-Gómez (1992) and Shaviv (2001) classified CRF according to the mechanism of delaying nutrient transfer to the substrate: materials coated by polymers or resins, low-solubility organic substances (urea-formaldehyde, isobutylen diurea) or nutrients in a carrier matrix (waxes, peat, vermiculite, lignin, etc.). Most trials conducted to test the effectiveness of these fertilizers concluded that the amount of nutrients required is significantly reduced compared to conventional fertilizers, highlighting the energy savings and the improved use of N, minimizing its losses (Shoji and Kanno, 1994;Shaviv, 2001Shaviv, , 2001Hangs et al, 2003;Chen et al, 2008;Sato and Morgan, 2008;Entry and Sojka, 2008;Hyatt et al, 2010;Wilson et al, 2010). Another reason for recommending the use of CRF is to prevent the emission of N 2 O from N fertilization practices, due to its role in climate change (Cheng et al, 2006;Jingyan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ESN produced lower winter wheat straw yield than UAN for 75% of the site-years. In a 3-yr potato yield trial conducted in loamy sand soil in Minnesota, Hyatt et al (2010) examined crop yield and N 2 O emissions using a split application of NCU compared with a single application of two different CRU fertilizers. They found that potato yield was not significantly different among fertilizer sources but N 2 O emissions were significantly lower using the CRU fertilizer compared with the conventional split application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The intent is to reduce the risk of N losses, thus improving N use efficiency and reducing potential negative environmental damage. Several studies have examined the environmental and agronomic impacts of using CRU with varied results (Nelson et al 2008Beres et al 2010;Cahill et al 2010;Hyatt et al 2010;Malhi et al 2010;Mckenzie et al 2010;Blackshaw et al 2011;Ziadi et al 2011;Yang et al 2011).…”
mentioning
confidence: 99%